The Interactions Between Stock and Bond Markets in Selected European Economies During the COVID-19 Pandemic - Kovářík, Tomáš (2025)
This thesis examines stock–bond co-movement in eight European countries, with a focus on the COVID-19 pandemic. Using DCC-GARCH, fixed-effects regressions, Granger causality, and wavelet coherence, it shows that inflation and short-term interest rates are the main drivers: high inflation and restrictive policy induce positive correlations, while accommodative regimes sustain negative ones. Other factors such as GDP growth, unemployment, and current accounts are relevant only in certain periods. During COVID-19, bonds briefly acted as safe-haven assets before inflation and tightening shifted correlations upward. The results underline the regime-dependent nature of stock–bond relationships and their importance for diversification and monetary policy.